Some Salient Features of Guatemala's Public and Private School Sectors - Ruano, Carlos R. (Education Policy Analysis Archives, 2003)
The purpose of this article is to analyze the formulation and implementation of educational policy processes in relation to private schools in Guatemala. Specifically, how bilingual education is defined and implemented in the private education sector in Guatemala City where the largest number of privately run establishments exist. Given the great deficits in the provision of educational coverage in the public sector, there has been an explosive expansion of private institutions which have very different levels of quality. Through an analysis of the administrative processes within the Guatemalan Government in general and its Education Ministry in particular as well as of the governance arrangements existing in the private school sector, an overall view of the curricular and policy decisions taken by private schools in the formulation and implementation of bilingual education is presented. This study was based on a sample of six private schools which cater to higher income segments of Guatemala City’s student population. Some of the relevant findings of this study include, the existence of a situation of quasi autonomous institutional functioning of the private sector, extreme differentials in the quality of services provided, inadequate levels of teacher and school administrator’s training as well as lack of cooperation between public and private sector schools.